Our Surgical Results in Popliteal and Infrapopliteal Artery Injuries: 21 Cases without Amputation - Burak Tamteki̇n; Güler Gülsen Ersoy (Emergency Medicine International)
Objectives. Popliteal and infrapopliteal artery injuries have significant morbidity and mortality rates, especially in terms of amputation. In our study, we aimed to evaluate patients who operated due to popliteal and infrapopliteal vascular injuries in our clinic. Patients and Methods. Between 2016 and 2023; 21 patients who were operated in our clinic due to popliteal and infrapopliteal artery injuries were retrospectively evaluated. Results. 2 of the patients were female (9.5%) and 19 were male (90.5%). Age ranges were 21–78. The causes of injury were gunshot wounds in 9 patients (42.86%), blunt trauma in 7 patients (33.33%), and sharp object injuries in 5 patients (23.80%). Reversed saphenous vein interposition in 7 patients (33.33%), primary repair in 6 patients (28.57%), 6 mm polytetrafluoroethylene graft (PTFE) interposition in 3 patients (14.28%), end-to-end anastomosis in 2 patients (9.52%), saphenous-PTFE composite graft interposition in 2 patients (9.52%), and embolectomy in 1 patient (4.76%) were performed. Arterial ligation was not performed. Simultaneous orthopedic intervention was performed in 8 patients. Fasciotomy was performed in 3 patients. Venous repair was performed in 5 patients with venous injuries. Vein ligation was not performed. Mortality was observed postoperatively in 1 patient. No patient developed amputation. Foot drop developed with nerve damage in 2 patients. Conclusion. Mortality and morbidity rates may increase in popliteal and infrapopliteal artery injuries in cases of hemodynamic disorder, simultaneous bone fracture, multivessel injury, and nerve transection. These rates can be reduced by appropriate surgical repair and ensuring hemodynamic stability.